Synthesis and Properties of Copper(II)-Ferrocene Formylated Curcumin - Huai, Qiyong; Yu, Junqiang; Xu, Xiushang; Miao, Jinlai; Wang, Zongling (Asian Journal of Chemistry, 2013)
A mononuclear (1:1) copper complex of ferrocene formylated curcumin was synthesized. The complex was characterized by elemental analysis, IR and UV-visible spectra. The copper atom is coordinated through the keto-enol group of ferrocene formylated curcumin along with one acetate group and one water molecule. Its electrochemical property was examined by cyclic voltammogram and antibacterial activities to Staphylococcus aureus was detected by bacteriostatic experiment. Cyclic voltammetric studies of complex showed a reversible Cu2+/Cu+ couple redox wave at oxidation potential 0.142 V and at reduction potential 0.116 V, respectively, appearing from -1 to 1 V. The peak separation (DP) is 26 mV and the peak current ratio (Ipa/Ipc) is 1.01, which expected to show superoxide dismutase activity. Bacteriostatic experiment showed the antibacterial activity of complex is stronger than that of curcumin.